2022
DOI: 10.1101/2022.12.06.519290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleep-related consolidation and generalizability of motor skills learned by physical practice, motor imagery and action observation

Abstract: Sleep benefits the consolidation of motor skills learned by physical practice, mainly through periodic thalamocortical sleep spindle activity. However, motor skills can be learned without overt movement, either through motor imagery or action observation. Here, we investigated whether sleep spindle activity also supports the consolidation of non-physically learned movements. Forty-five electroencephalographic sleep recordings were collected during a daytime nap after motor sequence learning by physical practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…However, the post hoc analysis failed to detect significant changes in performance from the test to the retest ( M Test = 302 and M Retest = 284, p = 0.18), thus revealing a sleep-based stabilization rather than an enhancement of the consolidated memory [36]. At the group level, the absence of delayed performance changes over the retention interval may be due to the non-averaging of performance blocks during training and testing sessions, since block averaging is known to be a confounding factor that accounts for, and further exacerbates, the offline gains [10,37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the post hoc analysis failed to detect significant changes in performance from the test to the retest ( M Test = 302 and M Retest = 284, p = 0.18), thus revealing a sleep-based stabilization rather than an enhancement of the consolidated memory [36]. At the group level, the absence of delayed performance changes over the retention interval may be due to the non-averaging of performance blocks during training and testing sessions, since block averaging is known to be a confounding factor that accounts for, and further exacerbates, the offline gains [10,37].…”
Section: Resultsmentioning
confidence: 99%
“…A large body of research has provided substantial evidence that sleep, and spindles in particular, facilitates neuroplasticity and the associated consolidation of both declarative and motor memories [19,41]. Recent empirical research and theoretical frameworks have also outlined the essential contribution of the clustering and hierarchical rhythmicity of sleep spindle activity in the memory consolidation process [9,14,16], especially during NREM2 sleep when it relates to the consolidation of a newly learned motor skill [5,7,13,37]. The present results thus confirm the positive effects of NREM2 sleep spindles in the consolidation of motor sequences.…”
Section: Discussionmentioning
confidence: 99%
“…However, in young adults, the affordance of sleep in the post-learning interval, either immediately or even 12 h and later after training, was shown to be a critical factor in the advancement and expression of consolidation phase gains after actual, physical, practice 20 , 28 . A recent study of key press (typing movements) sequence learning 27 reports that a 3 h long interval containing ~ 90-min of daytime nap did not result in significant delayed gains in the performance of the trainees, irrespective of whether participants had physical or mental practice, or trained by observation. This pattern of results suggests that a brief post-training interval, even one that includes an interval of daytime sleep, may not suffice for participants to express delayed gains in the performance of an observed sequence of finger movements.…”
Section: Discussionmentioning
confidence: 96%
“…However, each time-of-day condition was tested in a different group of participants, and, as the authors acknowledge, the potential influence of circadian rhythms on observation or motor imagery could not be ruled out. A recent study of typing-sequence learning 27 found no significant delayed gains in performance after training by observation, even when a brief interval of daytime (nap) was afforded, a result that may indicate that the length of the post-training interval rather than sleep may be important.…”
Section: Introductionmentioning
confidence: 95%
“…While the role of sleep in the skill-specific strengthening of motor memories during consolidation has been widely studied, evidence also showed that it can promote their generalization 7,13,14 . Indeed, recent theoretical evidence suggests that learning contexts creating conditions of memory instability may be critical for the generalization of motor skills 7,14 .…”
Section: Introductionmentioning
confidence: 99%